Stages of Early Adolescent Smoking Behavior Development in Tegal City, Indonesia: A Qualitative Study - Agus Susanto; Hartono; Ismi Dwi Astuti Nurhaeni; Drajat Tri Kartono (Future Science, 2021)
Early adolescent smoking behavior is a complex activity, which is formed through several stages. Not all teenagers who take the initiative to smoke will end up as active smokers. Many factors influence the formation of adolescent smoking behavior. The study aims to explore the stages of early teenagers' cigarette encounters until becoming a smoker in Tegal City, Province of Central Java, Indonesia. The researcher has done in-depth qualitative interviews with thirty-five participants. Study participants are male smoker adolescents. Data analysis used themes. The researcher broke the finding down into four stages. The four stages are to encounter cigarettes, try smoking, consider being a smoker, and enjoy smoking. Most teenagers learn from parents and peers about cigarettes. The reason for most adolescents' attempts was that older playmates threatened them. Peers and parents are crucial factors in shaping early adolescent smoking behavior. To stop smoking behavior, both parties must be actively interested in health promotion activities. The results of the study can be used as a reference in the preparation of adolescent smoking behavior prevention programs based on the condition of adolescents.